Herbal haircare as revealed by people in Jalgaon district, Maharashtra, India - Shubhangi, Pawar; Patil, D A (Journal of Experimental Sciences, 2012)
The paper deals with herbal hair consmetics used in tribal and rural areas of Jalgaon district (Maharashtra, India). The indigenous uses of 23 plant species belonging to 23 genera of 18 angiospermic families are presented. Each application is presented with its botanical name, vernacular name and family, their uses, methods of preparation of cosmetic product and mode of applications. Interestingly, 21 species out of 23 form additional reports for India. Scientific assessments of these applications are however desirable.